Polycyclic Aromatic Hydrocarbons (PAHs) in Muscles of Two Commercial Fish Species from Al-Kahlaa River in Missan Governorate, Iraq - Salih Hassan Jazza; Abdul-Hussain Y. Al-Adhub; Hamid T. Al-Saad (Marine Science Department Diponegoro University, 2015)
Al-Kahlaa River is one of main tributaries of the Tigris River in Missan city and rises from northwest side of Amara city and continues to flow in the direction to the east of city center. Two commercial fish species (Liza abu and Carassius auratus) were collected seasonally (autumn, winter, spring and summer) during period from 2012 to 2013 from Al-Kahlaa River in Missan governorate. The concentrations of Polycyclic Aromatic Hydrocarbons (PAHs) in fish muscles were determined in the laboratories of Nihran Omer (South Oil Company in Basrah province), using Gas Chromatography. Total concentrations of PAHs in muscles of L. abu ranged between 2.301 and 16.661 ng.g-1 dry weight during winter and summer respectively and in C. auratus between 1.095 and 8.675 ng.g-1 dry weight during winter and summer, respectively. Results of this study revealed that high molecular weight of PAHs were more than low molecular weight in both fish species, and according to ratios of Low molecular weight Polycyclic Aromatic Hydrocarbons (LPAHs) to High molecular weight Polycyclic Aromatic Hydrocarbons (HPAHs), Benzo(a) Anthracene /(Benzo(a) Anthracene+ Chrysene) BaA/(BaA+Chr),Indeno (1,2,3-cd) pyrene /(Indeno (1,2,3-cd) pyrene + Benzo (ghi) perylene) InP/(InP+BghiP) and Fluoranthene/Pyrene (Fl/Py), they certainly reflected that the PAHs sources in both species are pyrogenic as a main sources and petrogenic as a small part. Also results of this study revealed the presence of seasonal variations in total concentrations of PAHs in both fish species. The study area was generally contaminated with hydrocarbons and continuous consumption of food from this area may pose public health hazards. Keywords: polycyclic aromatic hydrocarbons, PAHs, fish, pollution Al-Kahlaa adalah salah satu anak sungai utama Sungai Tigris di kota Missan dari sisi barat laut kota Amara dan terus mengalir ke arah ke timur dari pusat kota. Dua spesies ikan komersial (Liza abu dan Carassius auratus) diperoleh pada musim berbeda (gugur, dingin, semi dan panas) selama periode 2012-2013 dari Al-Kahlaa. Konsentrasi polisiklik aromatik hidrokarbon (PAH) pada otot ikan dianalisis di laboratorium Nihran Omer (South Oil Company di provinsi Basrah), menggunakan Gas Chromatography. Total konsentrasi PAH pada otot L. abu berkisar antara 2,301 dan 16,661 ng.g-1 berat kering pada musim dingin dan musim panas. Sedangkan pada C. auratus antara 1,095 dan 8,675 ng.g-1 berat kering pada musim dingin dan musim panas. Hasil penelitian ini menunjukkan bahwa berat molekul tinggi PAH lebih dari berat molekul rendah pada kedua spesies ikan, dan menurut rasio berat molekul rendah polisiklik aromatik hidrokarbon (LPAHs) untuk berat molekul tinggi polisiklik aromatik hidrokarbon (HPAHs), Benzo (a ) Anthracene / (Benzo (a) Anthracene + Chrysene) BAA / (BAA + Chr), Indeno (1,2,3-cd) pyrene / (Indeno (1,2,3-cd) pyrene + Benzo (ghi) perylene) InP / (InP + BghiP) dan fluoranthen / Pyrene (Fl/Py), hal ini mencerminkan bahwa sumber PAH di kedua spesies adalah pirogenik sebagai sumber utama dan petrogenic sebagai bagian kecil. Hasil penelitian ini juga mengungkapkan adanya variasi musiman total konsentrasi PAH di kedua spesies ikan. Daerah penelitian umumnya terkontaminasi dengan hidrokarbon sehingga konsumsi makanan dari daerah ini secara berkelanjutan dapat menimbulkan bahaya kesehatan masyarakat. Kata kunci: polisiklik aromatik hidrokarbon, PAHs, ikan, polusi